2020
DOI: 10.1186/s12870-020-02463-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional MYB transcription factor gene HtMYB2 is associated with anthocyanin biosynthesis in Helianthus tuberosus L

Abstract: Background: Tuber color is an important trait for Helianthus tuberosus L. (Jerusalem artichoke). Usually, purple tubers with high anthocyanin content are more nutritious than white tuber. But, the molecular mechanism underlying it is unknown. Results: In the current study, high-throughput RNA-sequencing was used to compare the transcriptomes between plants with tubers with red or white epidermis. Compared with the white-skinned tubers of cultivar QY3, anthocyanin biosynthesis structural genes had greater expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Tobacco is one of the most widely studied model plants in verifying the functions of anthocyanin regulators (Vimolmangkang et al, 2013 ; Huang et al, 2016 ; Zhao et al, 2022 ). For example, HtMYB2 (Gao et al, 2020 ), EsMYB9 (Huang et al, 2017 ), AaMYB2 (Li et al, 2016 ), and IbMYB1a (An et al, 2015 ) were found to regulate tobacco anthocyanin biosynthesis to varying degrees. Similarly, in this study, overexpression of AcMYB1 in tobacco displayed striking changes in anthocyanin accumulation in both vegetative and reproductive tissues at various developmental stages ( Figures 6A–L ).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco is one of the most widely studied model plants in verifying the functions of anthocyanin regulators (Vimolmangkang et al, 2013 ; Huang et al, 2016 ; Zhao et al, 2022 ). For example, HtMYB2 (Gao et al, 2020 ), EsMYB9 (Huang et al, 2017 ), AaMYB2 (Li et al, 2016 ), and IbMYB1a (An et al, 2015 ) were found to regulate tobacco anthocyanin biosynthesis to varying degrees. Similarly, in this study, overexpression of AcMYB1 in tobacco displayed striking changes in anthocyanin accumulation in both vegetative and reproductive tissues at various developmental stages ( Figures 6A–L ).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter sequences of NsMYB1 were isolated from RF and BF by Thermal asymmetric interlaced polymerase chain reaction (TAIL-PCR) [50]. The functional domain in NsMYB1 promoter sequences were analyzed based on BDPG (http://www.fruit y.org/seq tools/promoter.html) [51].…”
Section: Isolation Of Promoter Regionmentioning
confidence: 99%
“…Based on the genome data, Wang et al [31] identified a total of 229 MYB members that could be further divided into 23 subfamilies, but they did not focus on the anthocyanin biosynthesis related members; Zhao et al [17] identified 11 MYBs from blueberry fruits through homologous protein searching, using Arabidopsis, apple, grape and strawberry MYBs belonging to the MBW complex as queries. Recently, many ABRMs have been identified and functionally approved in various plant species, such as Arabidopsis [36], Helianthus tuberosus [37], monkeyflower [38], Eutrema salsugineum [39], Freesia hybrida [40], grape hyacinth [41], apple [42] and so on. In this study, for the exploration and characterization of blueberry ABRMs, we identified the blueberry ABRMs by homologous searches against the blueberry protein data provided by the highbush blueberry genome project using the reported ABRMs from some other plant species as queries, characterized their sequences, and investigated their corresponding genes' expression patterns in blueberry fruits at five different ripening stages, based on our previously obtained transcriptome data and quantitative real time PCR (qRT-PCR) analysis.…”
Section: Introductionmentioning
confidence: 99%